Experimenting with prototype system DLVK via different approach - Shah, Asim Ali (Knowledge-based systems, 2006)
Planning allows one to sequence a series of actions to achieve a certain goal. In this paper, we present a short overview of the Disjunctive logic programming under the answer set semantics Then we use the proposed DLV K planning system against a well-known blocks world planning domain for fully and partially specified initial state facts and the system performance is checked in the run time CPU seconds while increasing the plan length which are the number of steps presenting the plan quality together with security check feature for each plan to know whether the plan generated is secure. Blocks world planning has been widely investigated by planning researchers, primarily due to its simplicity and also because it captures several of the relevant difficulties that are involved in a typical planning domain. The work presented in this paper contributed mainly as a technique compatible with the extensions and improvements of the existing system rather than as a concrete planning system.